On-demand cooperative spectrum sensing and channel allocation in cognitive wireless networks - Bao-gang LI; Yuan-an LIU; Kai-ming LIU (Tongxin xuebao)
Combining of the broadcast feature of control messages in the route discovery and maintenance process,a method to make the mutual information of the spectrum sensing and channel allocation into the route control messages was proposed.The information exchange of cognitive users is started by the route discovery process,and then creates the node cluster for cooperative sensing along the route path,which is maintained by the route maintenance messages.In order to maximize the network capacity of cognitive users,proposed jointly design of the spectrum sensing and the channel allocation.Simulation analysis showed that the overhead of information exchange for cognitive users reduce,and ease the bottleneck effects of the control channel in cognitive wireless networks,meanwhile efficiently re-use the idle spectrum.